CIL:10602, Leishmania mexicana, Mus musculus, macrophage, parasite. In Cell Image Library ... - Wheeler, Richard (UC San Diego Library Digital Collections, 2021)
Macrophage cell line cell infected with Leishmania mexicana. Five amastigotes can be seen within a single large parasitophorous vacuole in the macrophage. Raw 264.7 cells (a leukaemic mouse macrophage line) were infected with amastigote form Leishmania mexicana (WHO strain MNYC/BZ/62/M379) at an MOI of 10 and maintained in RPMI for 4 days. Cells were fixed with 2% paraformaldehyde, and DNA was labelled with propidium iodide following incubation with 50 ug/ml RNaseA for 30 min at room temperature. Z stack of 93 images with a z spacing of 0.194 um captured with a 100x/1.4 NA objective lens on a DM5500 B epifluorescence microscope (Leica) with an Orca cooled CCD camera (Hamamatsu). Note there is a phase channel image that is not currently displayed, but can be turned on in the full viewer mode. ... : Preparation: formaldehyde fixed tissue Relation to intact cell: permeabilized tissue Item type: recorded image Imaging mode: fluorescence microscopy Parameter imaged: fluorescence emission; optical path length gradient Source of contrast: differences in adsorption or binding of stain; boundaries between regions with different refractive index Visualization methods: propidium iodide Processing history: unprocessed raw data Data qualification: Raw;spatialmeasurements;intensitiesquantitation ...